Penggunaan Supervisi Klinis dalam Upaya Meningkatkan Kemampuan Guru Menggunakan Model Pembelajaran Inovatif di SD Negeri 166/X Pandan Jaya Semester Ganjil Tahun Pelajaran 2022/2023 - Armaidi Armaidi (Journal on Education, 2023)
This study aims to disclose information and discuss the use of clinical supervision in an effort to improve teachers' abilities to use innovative learning models at SD Negeri 166/X Pandan Jaya odd semester in the 2022/2023 school year. This research is included in the type of School Action Research (PTS). This research was conducted at SD Negeri 166/X Pandan Jaya. This research was conducted at SD Negeri 166/X Pandan Jaya. The time of this research was carried out in the odd semester of the 2022 - 2023 school year which began in July 2022. The subjects in this study were 7 teachers at SD Negeri 166/X Pandan Jaya. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using instrument sheets, observation and reflection. The data analysis technique used in this study is to use the proportion formula. The results of this study indicate that using clinical supervision can improve teachers' abilities to use innovative learning models at SD Negeri 166/X Pandan Jaya odd semester in the 2022/2023 school year. So because of that clinical supervision is very suitable to be used as a way to improve the ability of these teachers, one of which is in using learning models.